Rapid RT-PCR identification of SARS-CoV-2 in screening donors of fecal microbiota transplantation - Sara Scaglione; Franca Gotta; Daria Vay; Christian Leli; Annalisa Roveta; Antonio Maconi; Andrea Rocchetti (Heliyon, 2023)
Since its first appearance in late 2019 in Wuhan, China, severe acute respiratory syndrome caused by Coronavirus 2 (SARS-CoV-2) has had a major impact on healthcare facilities around the world. Although in the past year, mass vaccination and the development of monoclonal antibody treatments have reduced the number of deaths and severe cases, the circulation of SARS-CoV-2 remains high. Over the past two years, diagnostics have played a crucial role in virus containment both in health care facilities and at the community level. For SARS-CoV-2 detection, the commonly used specimen type is the nasopharyngeal swab, although the virus can be identified in other matrices such as feces. Since fecal microbiota transplantation (FMT) assumes significant importance in the treatment of chronic gut infections and that feces may be a potential vehicle for transmission of SARS-CoV-2, in this study we have evaluated the performance of the rapid cartridge-based RT-PCR test STANDARD™ M10 SARS-CoV-2 (SD Biosensor Inc., Suwon, South Korea) using fecal samples. The results obtained indicates that STANDARD™ M10 SARS-CoV-2 can detect SARS-CoV-2 in stool samples even at low concentration. For this reason, STANDARD™ M10 SARS-CoV-2 could be used as reliable methods for the detection of SARS-CoV-2 in fecal samples and for the screening of FMT donors.